Национальные основы в эпосе «Бахадыр - Алланазаров, Е. Национальные основы в эпосе «Бахадыр» поэта A (SCIENCE and SOCIETY, 2025)
The article discusses the reflection of folklore traditions and new realistic aspects in the epic poem "Ba- hadyr" by the people's poet A. Dabylov. In particular, the work's deep philosophical and patriotic aspects, especially the friendship of peoples, and its connection with reality are comprehensively scientifically analyzed.
Keywords: national epic traditions of folklore; folklore; landscape poetry (Nature Poetry) composition